PENGARUH HEATING RATE TERHADAP KARAKTERISTIK NILAI KALOR LIMBAH KULIT BUAH NIPAH (NYPA FRUTICANS (THUNB.) WURMB) PADA PROSES SLOW PIROLISIS - Yuniarti Yuniarti; Debora Ariyani; Eka Megawati (PETROGAS: Journal of Energy and Technology, 2020)
Nipah-Nipah plants grow mostly in the confluence of rivers and seas. This plant has the potential to maximize all parts of the tree. Nipah fruit can be used for Nata Frutican and the basic ingredients for making flour. Unused fruit shells have a hard texture, similar to the texture of coconut shells. To increase the calorific value of this fruit peel charcoal, a pyrolysis process is carried out. The samples were separated from the following waste and dried in direct sunlight. The dry sample is crushed and then put into the combustion reactor. Pyrolysis was carried out at a constant temperature of 500°C with variations in the heating rate of 2°C/minute, 4°C/minute, 6°C/minute, 8°C/minute, and 10°C/minute and holding time for 1 hour. The results showed that the calorific value decreased with increasing heating rate. The highest calorific value is at the lowest heating rate. The calorific value at a heating rate of 2°C/minute is 6841, 02 cal/gram. ; 4°C/minute calorific value is 6811.59 cal/gram; 6°C/minute of 6745.07 cal/gram; 8°C/minute is 6656.59 cal/gram and at 10°C/minute is 6570.41 cal/gram